Gifted education current perspectives and issues - Bakken, Jeffrey P.; Obiakor, Festus E.; Rotatori, Anthony F. (Advances in special education, 2014)
This volume addresses the most current perspectives and issues related to giftedness and is written by leaders in the field. An excellent resource for special educators, administrators, mental health clinicians, school counselors, and psychologists, this volume addresses the different educational issues that impact this population.